Indirect taxes and government inequality reduction: A cross-national analysis of the developed world - Mahler, Vincent; Jesuit, David (Journal of Income Distribution®, 2018)
This article explores the role of indirect taxes in helping to finance public social transfers in the developed countries, with special attention to the seeming paradox whereby countries whose social benefit programs provide the most inequality reduction tend to finance those programs with the most regressive tax mix. It finds that the share of indirect taxes in a country’s GDP and the degree to which market inequality is reduced by public social transfers are positively related, even controlling for other tax types, the share of the population that is elderly and the unemployment rate; that a large indirect tax burden is politically possible because of some combination of fiscal illusion and the fact that indirect taxes do not retard economic growth or investment; and that the high indirect taxes that finance public social transfers are often the product of a political process in which democratic corporatism, institutional structures and union density play key roles. The article concludes with a discussion of the incidence of indirect taxes, finding that their regressive effect is outweighed by the redistribution accomplished by the public social transfers they help to finance.